Sulfosalts and Sulfates in the Epithermal Au-Ag-Te Emmy Deposit (Khabarovsk Territory, Far East of Russia): Implications for the Mineralization Process - Tamara Yu. Yakich; Panagiotis Voudouris; Darya V. Levochskaia; Alexey K. Mazurov; Mikhail V. Shaldybin; Yuriy M. Lopushnyak; Alexey S. Ruban; Evan Dasi; Prokopiy N. Maximov; Ekaterina A. Sinkina; Ksenia V. Bestemianova; Maxim A. Rudmin (Geosciences)
This study considers the features of the chemical composition, internal structure, and oscillatory zoning of sulfosalts and sulfates in the epithermal high–intermediate-sulfidation-type Au-Ag-Te Emmy deposit (Khabarovsk Territory, Russia). In Emmy deposit, sulfosalts primarily represent goldfieldite, probably corresponding to a high-sulfidation (HS) mineral association replaced bytennantite–tetrahedrite group minerals. The latter is associated with tellurides and native tellurium, corresponding to an intermediate-sulfidation (IS)-type ore assemblage and suggesting an increasing influx of Te, Sb, and As in the system. Goldfieldite is replaced by native tellurium and tellurides along its growth zones, and is characterized by oscillatory zoning. The replacement of goldfieldite by mercury, nickel, lead, and copper tellurides indicate a new influx of native gold, native tellurium, and gold–silver tellurides into the open mineral-forming system. At deeper levels of the Emmy deposit, an advanced argillic alteration assemblage includes aluminum phosphate–sulfate (APS) minerals, represented by members of the svanbergite–woodhouseite series. Element mapping of the studied APS mineral grains indicated three distinct areas recording the evolution of the hydrothermal system in the Emmy: an oscillatory-zoned margin enriched in sulfur, lead, and barium, corresponding to the late influx of IS state fluids related to gold and tellurides; an intermediate part, which is leached and corresponds to the HS mineralization stage; and the central part of the grains, which is enriched in cerium, calcium, and strontium, resulting from a replacement of magmatic apatite in the pre-ore alteration stage. The leached zone between the core and rim of the APS grains is related to a change in crystallization conditions, possibly due to the mixing processes of the fluids with meteoric water. Barite, found in the upper level of the advanced argillic hypogene alteration assemblage, is also characterized by oscillatory zoning, associated with the enrichment of individual zones in lead. Micron gold particles associated with barite are confined to their lead-enriched zones. The study of fluid inclusions in quartz within the Emmy deposit showed the hydrothermal ore process at a temperature of 236–337 °C. Homogenization temperatures for quartz–pyrite–goldfieldite mineral association vary within 337–310 °C and salinity varies within 0–0.18 wt.%NaCl equivalent, and for gold–silver–telluride–polymetallic mineral association, they decrease and vary within 275–236 °C and salinity slightly increases from 0.18 to 0.35 wt.%NaCl equivalent. This study demonstrates that the nature of oscillatory zoning in sulfosalts and sulfates in the Emmy deposit results from an external process. Such a process is of fundamental importance from a genetic point of view.